Impact of the updating of clinical guidelines for RSV bronchiolitis on the use of diagnostic testing and medications in tertiary hospitals in Colombia - Buendia Rodriguez, JA; Patino, DG (African Field Epidemiology Network, 2022)
Introduction: the incidence of Respiratory Syncytial Virus (RSV) infection and their variability in the clinical management, make this disease a candidate for monitoring adequate use of resources. The objective of this study was to evaluate the impact of the updating of clinical guidelines for RSV bronchiolitis on the use of diagnostic testing and medications in tertiary hospitals in Colombia.